Short-Term Oral Quercetin Supplementation Improves Post-exercise Insulin Sensitivity, Antioxidant Capacity and Enhances Subsequent Cycling Time to Exhaustion in Healthy Adults: A Pilot Study - Tsao, Jung-Piao; Bernard, Jeffrey R.; Hsu, Hsiu-Chen; Hsu, Chin-Lin; Liao, Su-Fen; Cheng, I-Shiung (Frontiers in Nutrition, 2022)
Aim Quercetin has been reported to have antioxidant and anti-inflammatory properties on health promotion in human studies. The main purpose of this study was to investigate the effect of short-term oral quercetin supplementation on post-exercise whole-body energy metabolism. This study also aimed to determine the effects of supplementation on oxygen stress, inflammation, muscle damage, and high-intensity cycling exercise performance. Method Twelve healthy participants, physically active students, were recruited to perform a randomized, single-blind crossover study. All subjects completed 7-days of quercetin (quercetin:1,000 mg per day for 7-days) and placebo supplementation in a randomized order. Supplement/placebo was combined with exercise consisting of 70% V̇O2max cycling for 60-min, followed by 3-h of recovery, then a subsequent single bout of cycling exercise with 75% V̇O2max to exhaustion. Time to exhaustion, indicators of muscle damage, as well as blood and gaseous parameters relating to energy metabolism, oxidative stress, inflammatory response, respectively, were determined. Results The results showed that 7-day quercetin supplementation significantly attenuated the post-exercise glucose-induced insulin response, increased total antioxidant capacity (TAC) and superoxidase dismutase (SOD) activities, and mitigated malondialdehyde (MDA) levels during the recovery period (p < 0.05). While subsequent 75% V̇O2max cycling performance was significantly improved after quercetin treatment and accompanied by lower responses of interleukin 6 and creatine kinase at 24-h. However, it’s noted that there were no significant responses in glucose, respiratory exchange rate, tumor necrosis factor-α (TNF-α), myoglobin, and high sensitivity C-reactive protein between quercetin and placebo trials. Conclusion Our findings concluded that 7-day oral quercetin supplementation enhances high-intensity cycling time to exhaustion, which may be due in part to the increase in whole-body insulin-stimulated glucose uptake and attenuation of exercise-induced oxygen stress and pro-inflammation. Therefore, quercetin may be considered an effective ergogenic aid for enhancing high-intensity cycling performance among young adults.